HOMO energy level regulation of novel conjugated copolymers for polymer solar cells. (27th August 2015) - Zhang, Jianfeng; Wang, Sheyu; Liu, Qida; Liu, Zhiyang; Peng, Ruixiang; Ge, Ziyi
<x xml:space="preserve">Abstract</x> Novel donor–acceptor conjugated copolymers were synthesized, and the HOMOs were regulated to high open circuit voltage and wide spectral absorption.